ANALISIS AKTOR PEMBENTUKAN BUMDES PAGEDANGAN CAHAYA MADANI DALAM PERSPEKTIF GOVERNANCE - Sari, Yasmine Permata; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2017)
Developing Indonesia’s rular area is one of Indonesia’s priorities agenda. The goal is to improve rular communities economy and overcome the gap of national development. This can be realized by establish a BUMDes.In the reformation era, policy formulation should be based on governance. The problem is how the governance role actors in the policy formulation of BUMDes establisment process? This study purposeto determine role of state, society and private actor in the policy formulation of BUMDes establishment and create stategies of third actor. This research used a descriptive type-qualitative aproach. The result found that the actors in in policy formulation of BUMDes establisment show its role according with the governance perspective, altough not as ideal as expected. The village goverment role is to accountability every decision by a clear proof, design a concept of business unit and mobilize society and private actors. The role of society is participate and supervise every process of policy formulation process. The private role is attending a forum of policy formulation and cooperate with village goverment of BUMDes establishment.